Third Five Year Plan 1961-66 Statements Showing the Actual Expenditure - Government of Kerala (Government of Kerala, 1967)
The Third Five-Year Plan (1961–1966) implemented by the Government of Kerala represented a significant phase of planned socio-economic development aimed at strengthening infrastructure, agriculture, industry, and social welfare within the state. With a targeted expenditure of approximately Rs. 17,000 lakhs, the plan ultimately recorded an actual expenditure of about Rs. 18,231.01 lakhs, indicating an expansion of development initiatives beyond initial expectations. A substantial share of financial resources was directed toward irrigation and power, which together accounted for the largest sectoral investment, reflecting the government's priority to enhance energy generation and water management for agricultural and industrial growth. Agricultural programmes, although central to the development agenda, achieved around 82 percent of the planned target, highlighting continuing structural challenges in the sector. Community development and cooperative initiatives demonstrated notable progress, supporting rural development and strengthening local institutional participation. The plan also emphasized industrial and infrastructure development, including improvements in transport, communications, and mining, while simultaneously promoting traditional industries such as coir and handicrafts to generate employment and sustain local economies. Social services formed another major component of the plan, with significant investments in education, healthcare, medical education, and welfare programmes for Scheduled Castes, Scheduled Tribes, and other backward communities, thereby reflecting a strong commitment to social equity and human development. Additional attention was given to technical education, urban improvement projects, and the expansion of medical colleges and hospitals, illustrating a broader strategy to build human capital and improve living standards. Despite some discrepancies between allocations and actual expenditures in certain sectors, the plan overall demonstrated a balanced approach that combined infrastructural expansion, economic diversification, and social welfare initiatives. Consequently, Kerala’s Third Five-Year Plan stands as an important developmental framework that sought to address economic growth, rural transformation, and social upliftment, offering valuable insights into the challenges and achievements of state-level planning during this period.
Government of Kerala
Government of Kerala
Keywords: State Five Year Plan; Kerala Development Planning; Irrigation and Power Development; Agricultural Programmes; Community Development and Cooperation; Industrial and Infrastructure Growth; Social Services Expansion; Health and Medical Education; Coir and Handicrafts Development; Welfare of Backward Classes; Technical Education Advancement; Public Expenditure Analysis